Effect of Solvent Removal on Microtensile Bond Strength of Etch and Rinse Systems under Vigorous Application to Wet and Dry Dentin - Mansoreh Mirzaei; Esmaeil Yassini; Farzaneh Aghagani; Narges Ezzati Givii; Mohammad Javad Kharazi Fard (Islamic Dental Association of Iran, 2014)
Background and Aim : Adhesive systems are commonly used for restorative dental procedures. Solvent removal my be effective for increasing the microtensile bond strength of etch and rinse systems to dentin. The aim of this study was to evaluate the effect of solvent removal on microtensile bond strength of etch and rinse systems to wet and dry dentin .   Materials and Methods : This in-vitro study was conducted on 40 intact human extracted third molars . A flat superficial dentin surface was exposed by wet abrasion. The specimens were randomly assigned to five groups. Two coats of the solvent-based (SB) and solvent-free (SF) adhesives were applied to dry (D) or rewetted (W) surfaces, under vigorous rubbing action after phosphoric acid etching according to the manufacturer's instructions. The examined groups included: group one: adhesive with solvent on dry dentin, group two: adhesive without solvent on dry dentin, group three: adhesive with solvent on wet dentin, group 4: adhesive without solvent on wet dentin and group 5 (control group). After light curing (600mW/cm²/10 s), composite build-ups were constructed incrementally and specimens were stored in water (37 ° C/24 h). They were longitudinally sectioned in the "x" and "y" directions to obtain bonded sticks (1mm²) for immediate testing at a crosshead speed of 1 mm/min. The resultant bond strength was expressed for different fracture patterns. The microshear bond strength test was carried out in a Universal Testing Machine. The data were analyzed using two-way ANOVA. All statistical analyses were performed using SPSS version 2 software. P<0.05 was considered significant .   Results : The highest bond strength was achieved in group 1 and the lowest in group 4 but the differences among groups in this respect were not statistically significant .   Conclusion : Within the limitations of this study, the results showed that presence of solvent was not essential to achieve high bond strength values to dry and wet dentin when applied vigorously .